Post-Heart Transplant Changes and Perceived Donor-Recipient Correspondences: A Scoping Review - Daniela Nigrelli; Marika Lo Monaco; Mariachiara Figura; Maria Rita Giammarinaro; Irene Zerilli; Israr Ahmad; Laura Iacorossi; Roberto Latina; Giuliano Anastasi (Journal of Clinical Medicine, 2026)
Background/Objectives: Heart transplantation is a life-saving treatment for advanced cardiac disease, but post-transplant adaptation may involve psychosocial, identity-related, and existential change. Some recipients interpret these changes as corresponding to donor characteristics, although the nature and evidence base of these reports remain unclear. This review mapped post-transplant changes reported by adult heart transplant recipients, perceived donor–recipient correspondences, and the explanatory frameworks proposed for these phenomena. Methods: A scoping review was conducted following the Arksey and O’Malley framework, Joanna Briggs Institute guidance, and PRISMA-ScR reporting standards. PubMed, Web of Science, Scopus, CINAHL, and PsychINFO were searched in August 2026. Quantitative, qualitative, mixed-methods, conceptual, opinion, and review articles were eligible. Findings were synthesized descriptively. Results: Sixteen sources published between 1992 and 2025 were included. Empirical studies reported changes in preferences, emotional and personality-related experiences, social and physical functioning, sexuality, identity and embodiment, sensory and memory-like experiences, and spirituality. Some changes were attributed by recipients to donor characteristics, whereas correspondences supported by independently obtained donor information were reported in a limited subset of studies. Proposed explanations ranged from psychological, pharmacological, physiological, and sociocultural processes to cellular, molecular, neurocardiac, energetic, and transpersonal hypotheses. Donor-transfer hypotheses were developed in the secondary literature and were not empirically established. Methodological quality varied substantially across sources. Conclusions: Post-transplant changes and perceived donor–recipient correspondences are meaningful phenomena, but current evidence does not support the transfer of donor memory, personality, or identity through the transplanted heart. Future prospective, longitudinal, and methodologically rigorous studies should distinguish reported experience, donor attribution, and proposed explanations.